Sweetened beverages, snacks and overweight: findings from the Young Lives cohort study in Peru - Alviso-Orellana, Claudia (2018)
Objective: To determine the association between consumption of snacks and sweetened beverages and risk of overweight among children. Design: Secondary analysis of the Young Lives cohort study in Peru. Setting: Twenty sentinel sites from a total of 1818 districts available in Peru. Subjects: Children in the younger cohort of the Young Lives study in Peru, specifically those included in the third (2009) and the fourth (2013) rounds. Results: A total of 1813 children were evaluated at baseline; 49·2 % girls and mean age 8·0 (sd 0·3) years. At baseline, 3·3 (95 % CI 2·5, 4·2) % reported daily sweetened beverage consumption, while this proportion was 3·9 (95 % CI 3·1, 4·9) % for snacks. Baseline prevalence of overweight was 22·0 (95 % CI 20·1, 23·9) %. Only 1414 children were followed for 4·0 (sd 0·1) years, with an overweight incidence of 3·6 (95 % CI 3·1, 4·1) per 100 person-years. In multivariable analysis, children who consumed sweetened beverages and snacks daily had an average weight increase of 2·29 (95 % CI 0·62, 3·96) and 2·04 (95 % CI 0·48, 3·60) kg more, respectively, than those who never consumed these products, in approximately 4 years of follow-up. Moreover, there was evidence of an association between daily consumption of sweetened beverages and risk of overweight (relative risk=2·12; 95 % CI 1·05, 4·28). Conclusions: Daily consumption of sweetened beverages and snacks was associated with increased weight gain v. never consuming these products; and in the case of sweetened beverages, with higher risk of developing overweight.